Effective inoculation technique for identification of resistance source in chilli (Capsicum annuum L.) against aflatoxin and management through Trichoderma species - K K Mishra, K K Pandey, R C Gupta, (Journal of Spices and Aromatic Crops, 2015)
The present study was carried out to develop an effective inoculation technique for screening chilli fruits against Aspergillus flavus and to identify the most effective bioagents against A. flavus to integrate them into management strategies. The study revealed that dipped method is better than pin- pricked method for creating maximum infection pressure on fruits and can be successfully utilized for screening against the pathogen. Artificial screening revealed that chilli varieties Tabasco, PBC-535, IIHR-10 and LCA-429 were resistant to A. flavus. Among three tested species of Trichoderma, T. viride was comparatively more effective against 21 isolates of A. flavus. All the Trichoderma species showed fungistatic behaviour against A. flavus even after 14 days of incubation. Differential response of Trichoderma species against A. flavus indicated distinct variability among the isolates of A. flavus collected from different regions of the country.